The Gothic and the Everyday Living Gothic - Piatti-Farnell, L.; Piatti-Farnell, L.; Beville, M.; Beville, M. (Palgrave Gothic, 2014)
The Gothic and the Everyday aims to regenerate interest in the Gothic within the experiential contexts of history, folklore, and tradition. By using the term 'living', this book recalls a collection of experiences that constructs the everyday in its social, cultural, and imaginary incarnations.